2012
DOI: 10.1371/journal.ppat.1002511
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis ClpP1 and ClpP2 Function Together in Protein Degradation and Are Required for Viability in vitro and During Infection

Abstract: In most bacteria, Clp protease is a conserved, non-essential serine protease that regulates the response to various stresses. Mycobacteria, including Mycobacterium tuberculosis (Mtb) and Mycobacterium smegmatis, unlike most well studied prokaryotes, encode two ClpP homologs, ClpP1 and ClpP2, in a single operon. Here we demonstrate that the two proteins form a mixed complex (ClpP1P2) in mycobacteria. Using two different approaches, promoter replacement, and a novel system of inducible protein degradation, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
222
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(234 citation statements)
references
References 35 publications
10
222
1
1
Order By: Relevance
“…Because we find that ADEPs both open the pores and activate M. tuberculosis ClpP1P2, it is plausible that rogue degradation of cellular proteins is also responsible for ADEP killing of M. tuberculosis (30). However, given that the M. tuberculosis clpX and clpC1 genes are essential (26)(27)(28), it also is possible that a loss-of-function mechanism contributes to ADEP killing. Specifically, ADEP disruption of the interaction between ClpP1P2 and an accessory AAA+ partner could lead to the accumulation of toxic proteins that are normally substrates of these Clp proteases (2).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because we find that ADEPs both open the pores and activate M. tuberculosis ClpP1P2, it is plausible that rogue degradation of cellular proteins is also responsible for ADEP killing of M. tuberculosis (30). However, given that the M. tuberculosis clpX and clpC1 genes are essential (26)(27)(28), it also is possible that a loss-of-function mechanism contributes to ADEP killing. Specifically, ADEP disruption of the interaction between ClpP1P2 and an accessory AAA+ partner could lead to the accumulation of toxic proteins that are normally substrates of these Clp proteases (2).…”
Section: Discussionmentioning
confidence: 81%
“…For example, Mycobacterium tuberculosis, a pathogenic actinobacterium, encodes cotranscribed clpP1 and clpP2 genes (24,25). The importance of Clp-family proteolysis in M. tuberculosis is highlighted by the facts that the clpP1, clpP2, clpX, and clpC1 genes are all essential and that mechanism-based ClpP inhibitors suppress growth (24,(26)(27)(28). Recent studies indicate that M. tuberculosis ClpP1 and ClpP2 form discrete heptameric rings that assemble into an active ClpP1P2 tetradecamer only in the presence of a ClpX or ClpC1 AAA+ partner and one additional factor, either protein substrates being actively translocated into the degradation chamber or N-blocked peptide agonists (23,29).…”
mentioning
confidence: 99%
“…For instance, MtbCFP-10 has been shown to interact with several other proteins, including ClpC1, an AAA-ATPase chaperone involved in protein translocation and quality control, and ClpC1 associates with the proteolytic component ClpP2 (33). It has recently been shown that ClpP1 and ClpP2 form a single proteolytic complex and function together in protein degradation, and both are required for bacterial viability in vitro and during infection (34,35). Thus, further studies of the roles of PTMs and other interacting factors in the heterodimer dissociation will facilitate our understanding of the MtbESAT-6-mediated pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of LmClpP2 with lactonebased inhibitors led to down-regulation of virulence without affecting viability (27). In contrast, both mycobacterial ClpP subunits are essential for bacterial survival, emphasizing defined functional roles of ClpP proteins among species (26,28).…”
mentioning
confidence: 99%